Factors Affecting the Land Use Change in Lam Dom Yai Subwatershed - Sribunkhum, Athiyaphan; Kunta, Karika; Arunyawat, Sunsanee (Burapha Science Journal, 2026)
Recently, drought in north eastern Thailand effects the agriculture production of Thailand due to it is a major cultivation area of economic crop. To improve the productivity, it is necessary to analyze land use changes, its impacts and related problems. This study aimed to study the land use change and its DPSIR framework components in Lam Dom Yai Subwatershed. This study was qualitative research integrated with land use change analysis. Semi-structure interviews were completed by different officers from various related offices to specify views, problems and finally, identify DPSIR components. The results showed that the agriculture in the study area had been changed considerably between 1999 to 2019. According to DPSIR concept, driving factor is an important starting factor for the changes such as market price of agricultural products, government policies, drought. Driving factors led to forest encroachment, chemical contamination in water or soil, lower income, etc. The important responses which are the solution for this situation included promotion of dry season non-rice crop cultivation, agricultural area protection, famers’awareness rising for agricultural adaptation . It will be help to reduce problems in the area.